Research into the anti-pulmonary fibrosis mechanism of Renshen Pingfei formula based on network pharmacology, metabolomics, and verification of AMPK/PPAR-γ pathway of active ingredients - Yan, Lu; Jiang, Min-Yue; Fan, Xin-Sheng (Journal of ethnopharmacology, 2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive disease with limited therapy. Renshen Pingfei Formula (RPFF), a classic Chinese medicine derivative formula, has been shown to exert therapeutic effects on IPF. The study aimed to explore the anti-pulmonary fibrosis mechanism of RPFF through network pharmacology, clinical plasma metabolomics, and in vitro experiment. Network pharmacology was used to study the holistic pharmacological mechanism of RPFF in the treatment of IPF. The differential plasma metabolites for RPFF in the treatment of IPF were identified by untargeted metabolomics analysis. By integrated analysis of metabolomics and network pharmacology, the therapeutic target of RPFF for IPF and the corresponding herbal ingredients were identified. In addition, the effects of the main components of the formula, kaempferol and luteolin, which regulate the adenosine monophosphate (AMP)-activated protein kinase (AMPK)/peroxisome proliferator-activated receptor γ (PPAR-γ) pathway were observed in vitro according to the orthogonal design. A total of 92 potential targets for RPFF in the treatment of IPF were obtained. The Drug–Ingredients–Disease Target network showed that PTGS2, ESR1, SCN5A, PPAR-γ, and PRSS1 were associated with more herbal ingredients. The protein–protein interaction (PPI) network identified the key targets of RPFF in IPF treatment, including IL6, VEGFA, PTGS2, PPAR-γ, and STAT3. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis acquired the main enriched pathways, and PPAR-γ involved in multiple signaling pathways, including the AMPK signaling pathway. Untargeted clinical metabolomics analysis revealed plasma metabolite variations in patients with IPF versus controls and before versus after RPFF treatment for patients with IPF. Six differential metabolites were explored as differential plasma metabolites for RPFF in IPF treatment. Combined with network pharmacology, a therapeutic target PPAR-γ of RPFF in IPF treatment and the corresponding herbal components were identified. Based on the orthogonal experimental design, the experiments showed that kaempferol and luteolin can decrease the mRNA and protein expression of α-smooth muscle actin (α-SMA), and the combination of lower dose can inhibit α-SMA mRNA and protein expression by promoting the AMPK/PPAR-γ pathway in transforming growth factor beta 1 (TGF-β1)-treated MRC-5 cells. This study revealed that the therapeutic effects of RPFF are due to multiple ingredients and have multiple targets and pathways, and PPAR-γ is one of therapeutic targets for RPPF in IPF and involved in the AMPK signaling pathway. Two ingredients of RPFF, kaempferol and luteolin, can inhibit fibroblast proliferation and the myofibroblast differentiation of TGF-β1, and exert a synergistic effect through AMPK/PPAR-γ pathway activation. [Display omitted] •Untarget clinical metabolomics analysis revealed the six differential metabolites, as plasma differential metabolites for RPFF in the treatment of IPF.•PPAR-γ is one of therapeutic targets for RPPF in IPF, and involved in AMPK signaling pathway integrated metabolomics and network pharmacology analysis.•The ingredients of RPFF, kaempferol and luteolin could inhibit TGF-β1 induced fibroblast proliferation and myofibroblast differentiation and exert a synergistic effect through AMPK/PPAR-γ pathway activation.